MINI FICTIONS FOR WRITING EXPOSITORY ESSAYS - Setyowati, Lestari; Sukmawan, Sony (English Teaching Journal, 2015)
Not many language teachers use literary works as teaching materials to teach language skills for their students. This is due to teachersâ common perception that literature has a high degree of difficulty to understand. As a result, the use of literary works is often ignored to teach language skills, especially writing. Basically, if teachers are able to select literary works in accordance with the purpose of teaching and use it well, literature can be a bridge to improve language skills, especially the skills of writing an expository text. This article aims to describe the stages of teaching to teach writing skills through mini-fiction for expository essay, tips on choosing fictions that can be used in the classroom, and the problems that may arise from the use of these mini fictions. There are three stages of learning to be conducted when teaching writing skills by using mini fictions, namely the preparatory stage, pre-writing, and writing phases. Using literary works will be able to sharpen the students language skills and their ability to think critically.